Carbon Quantum Dots The Role of Surface Functional Groups and Proposed Mechanisms for Metal Ion Sensing - Shabbir Hasan; Csapó Edit; Wojnicki Marek (2023)
Carbon dots (CDs) are zero-dimensional nanomaterials composed of carbon and surface groups attached to their surface. CDs have a size smaller than 10 nm and have potential applications in different fields such as metal ion detection, photodegradation of pollutants, and bio-imaging, in this review, the capabilities of CDs in metal ion detection will be described. Quantum confinement is generally viewed as the key factor contributing to the uniqueness of CDs characteristics due to their small size and the lack of attention on the surface functional groups and their roles is given, however, in this review paper, the focus will be on the functional group and the composition of CDs. The surface functional groups depend on two parameters: (i) the oxidation of precursors and (ii) their composition. The mechanism of metal ion detection is still being studied and is not fully understood. This review article emphasizes the current development and progress of CDs, focusing on metal ion detection based on a new perspective.
Keywords: Kémiai tudományok